Incorporating economics into fisheries management frameworks in Australia. (March 2017) - Emery, Timothy J.; Gardner, Caleb; Hartmann, Klaas; Cartwright, Ian
Abstract: A large gap has been identified between the current and optimal economic performance of wild-capture commercial fisheries in Australia. Economic approaches have the potential to assist fisheries to bridge this gap, such as bio-economic models that combine biology with fishing costs to evaluate the economic performance of a broad range of management measures. Economic objectives are prevalent in overarching Australian fisheries legislation, however economic data is often not collected and economic analyses or instruments not broadly applied. This paper reviews selected Australian fisheries to demonstrate the accrued economic benefits from applying formal bio-economic models and conducting empirical analyses of the impact of supply on product value. Challenges to the implementation and continued use of economic analyses and instruments are discussed including: (i) short-term transition costs and associated trade-offs between ecological, economic, social and political objectives; (ii) scarce logistical and financial capacity to collect and analyse economic data; (iii) a lack of desire among industry to change and transition to economic targets such as maximum economic yield (MEY), particularly when it is associated with lower catches; and (iv) a lack of economic literacy among fisheries managers and industry. It is contended that many of these challenges initially arise from an absence of clearly identified and prioritised objectives within overarching legislation and management plans. Once objectives are prioritised, limited resources can be allocated more efficiently to improve data collection, economic analysis and increase awareness as well as education of managers and industry. Highlights: There is a gap in current and optimal economic performance in Australian fisheries. Bio-economics and empirical analyses can assist in reducing this performance gap. Australian case-studies highlight the accrued benefits from economic approaches. Challenges to adoption include a lack of capacity, economic literacy and motivation. Prioritisation of explicit objectives can assist in addressing these challenges.